GCSE physics - Duncan, Tom (John Murray London, 2002)
The fourth edition of this comprehensive GCSE Physics text has been revised to cover the latest GCSE specifications. Additional material includes: the uses and dangers of radioactivity, nuclear stability and fundamental particles; and a new section of scientific ideas and evidence.